Starting out with visual C# - Gaddis, Tony (England Pearson, 2017)
Contents: introduction to computers and programming; introduction to Visual C#; processing data; making decisions; loops, files and random numbers; modularizing your code with methods; arrays and lists;...
Includes bibliography and index
Keywords: Công nghệ thông tin